2019
DOI: 10.1371/journal.pone.0218737
|View full text |Cite
|
Sign up to set email alerts
|

Tumor M2-PK: A novel urine marker of bladder cancer

Abstract: Purpose Bladder cancer is a “Warburg-like” tumor characterized by a reliance on aerobic glycolysis and expression of pyruvate kinase M2 (PKM2). PKM2 oscillates between an active tetramer and an inactive dimer. We aim to further characterize PKM2, in particular PKM2 dimer, as a urinary biomarker of bladder cancer and a potential target for treatment. Methods HTB-9, HTB-5, and UM-UC3 bladder cancer cells were assessed for proliferation under differential glucose levels us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
0
19
0
3
Order By: Relevance
“…Studies have shown that glycolysis is closely related to BCa development. For instance, upregulation of pyruvate kinase M2 is closely related to tumor growth and chemo-resistance and serves as a potential tumor marker for BCa monitoring [ 27 , 28 ]. Lactic acid dehydrogenase (LDHA) is a key enzyme in glycolysis and its upregulation in BCa promotes glycolysis, thereby facilitating tumor growth and immune evasion [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that glycolysis is closely related to BCa development. For instance, upregulation of pyruvate kinase M2 is closely related to tumor growth and chemo-resistance and serves as a potential tumor marker for BCa monitoring [ 27 , 28 ]. Lactic acid dehydrogenase (LDHA) is a key enzyme in glycolysis and its upregulation in BCa promotes glycolysis, thereby facilitating tumor growth and immune evasion [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zhou et al (2016) demonstrated that PKM2 is strongly expressed in urothelial carcinoma compared to adjacent normal tissue using both western blot and immunohistochemistry. Liu et al (2019) demonstrated that PKM2 levels in urine samples were substantially elevated in most patients with BCa. This indicates the association between the abnormal expression of PKM2 and BCa.…”
Section: Fewmentioning
confidence: 98%
“…Mechanisms delineated in other cancers indicate this is likely due to increased production of ROS by damaged mitochondria that are forced to use mitochondrial metabolism to generate the necessary biological intermediates [ 57 , 58 , 61 ] . Natural products targeting these enzymes have been discovered, and may serve as a source of chemotypes that can be further improved for targeting the Warburg Effect and overcoming cisplatin chemoresistance [ 57 , 62 ] .…”
Section: Cisplatin Based Chemotherapy In Bladder Cancermentioning
confidence: 99%
“…Shikonin and its enantiomer alkannin are napthoquinones derived from Lithospermum erythrorhizon in addition to some Alkanna plant species with noted anti-cancer activity [ 59 ] . Shikonin has direct anti-apoptotic activity in BCa cells and in xenograft tumor models and synergizes with cisplatin [ 59 , 62 ] . The mechanism appears to be through inhibition of PKM2 [ 59 ] .…”
Section: Natural Products - a Validated Source Of Biologically Active...mentioning
confidence: 99%